Change in parent and child psychopathology following obesity treatment and maintenance: A secondary data analysis. Issue 1 (16th August 2022) - Grammer, Anne Claire; Best, John R.; Fowler, Lauren A.; Stein, Richard I.; Kolko Conlon, Rachel P.; Balantekin, Katherine N.; Welch, R. Robinson; Perri, Michael G.; Epstein, Leonard H.; Wilfley, Denise E.
Summary: Background: General and eating disorder (ED) psychopathology are common among children and adults with overweight/obesity; few studies have examined their course of change throughout family‐based behavioural obesity treatment (FBT) and maintenance. Objectives: Examine: (1) the changes in the parent and child general and ED psychopathology during FBT and maintenance interventions; (2) the associations between change in psychopathology and change in weight among children or parents; (3) the associations between change in psychopathology within parent–child dyads. Methods: 172 parent–child dyads participated in 4‐month FBT and were subsequently randomized to one of three 8‐month maintenance interventions. General psychopathology (child anxiety/depressive symptoms, parent severity of global psychological distress), ED psychopathology (shape/weight concern), and percent overweight were assessed at baseline, post‐FBT, and post‐maintenance. Separate linear mixed‐effects models evaluated change in general and ED psychopathology, including an interaction between maintenance condition and time. Partial correlations examined associations between change in psychopathology and percent overweight among children or parents, and associations between change in psychopathology within parent–child dyads. Results: Among children, significant reductions were observed from baseline to post‐FBT in all forms of psychopathology and from post‐FBT to post‐maintenance in general psychopathology. Among parents, significant reductions were observed from baseline to post‐FBT in all forms of psychopathology; reductions were maintained from post‐FBT to post‐maintenance. There was no significant interaction between maintenance condition and time. Correlations between change in most forms of parent or child psychopathology and percent overweight were observed. Conclusions: Participation in FBT and maintenance was associated with improvements in general and ED psychopathology in both parents and children.